Social Network Analysis: a practical measurement and evaluation of Trust in a classroom environment - Giandini, Roxana Silvia (2012)
A social network is formed by a set of actors and the relationships established by them. SNA leads to distinct goals and perspectives of social network analysis and computer science. This paper introduces the study of social networks and their relationship with trust. We study the methods of detection and description of structural properties. This covers the concepts, methods and data analysis techniques of social networks analysis. After that, we introduce the concept of trust and its relation with social networks, because trust is a crucial factor in the interaction between actors. We use the Node XL tool and a case study in a classroom environment, to test the usability of SNA techniques considering metrics to measure trust and, significantly, the power of a tightly integrated metrics/visualization tool to spark insight and facilitate sense making to SNA.